Algebraische Zahlentheorie: vom 31.7. - 6.8. 1967 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1967)
R. Ayoub, Frankfurt; K. Barner, Stuttgart; H. Behr, Göttingen; H. Benz, Hamburg; H. Brückner, Hamburg; A. Brumer, Paris; J. W. S. Cassels, Cambridge; M. Eichler, Basel; W. D. Geyer, Heidelberg; N. Guthschmidt, Berlin; Ch. Hooley, Durham; T. Kubota, Nagoya; L. Kuipers, Delft; H. Jacobinski, Vendelsö; W. Jehne, Köln; K. Lakkis, Athen; H. W. Leopoldt, Karlsruhe; Elisabeth Lutz, Grenoble; J. Martinet, Grenoble; E. Maus, Hamburg; A. Menalda, Leiden; J. R. Merriman, Oxford; C. Meyer, Köln; L. Miller, Göttingen; J. Neukirch, Bonn; A. Pfister, Göttingen; P. Ribenboim, Kingston; A. Schinzel, Warschau; J. Sonn, Göttingen; Tamme, Hamburg; C. de Vreugd, Leiden; van der Wall, Leiden; R. Wilson, London; H. J. Zassenhaus, Worthington; H. G. Zimmer, Tübingen